Effects of skilled and unskilled training on functional recovery and brain plasticity after focal ischemia in adult rats - Pagnussat A.S. (2012)
Stroke is a leading cause of morbidity and mortality worldwide. Recovery of motor function after stroke can be modified by post-injury experience, but most of surviving patients exhibit persistence of the motor dysfunctions even after rehabilitative therapy. In this study we investigated if skilled and unskilled training induce different motor recovery and brain plasticity after experimental focal ischemia. We tested this hypothesis by evaluating the motor skill relearning and the immunocontent of Synapsin-I, PSD-95 and GFAP (pre and post-synaptic elements, as well as surrounding astroglia) in sensorimotor cortex of both hemispheres 6 weeks after endothelin-1-induced focal brain ischemia in rats. Synapsin-I and PSD-95 levels were increased by skilled training in ischemic sensorimotor cortex. The content of GFAP was augmented as a result of focal brain ischemia in ischemic sensorimotor cortex and that was not modified by rehabilitation training. Unexpectedly, animals remained permanently impaired at the end of motor/functional evaluations. Significant modifications in protein expression were not observed in undamaged sensorimotor cortex. We conclude that skilled motor activity can positively affect brain plasticity after focal ischemia despite of no functional improvement in conditions here tested. © 2012 Elsevier B.V. All rights reserved.